ANALISIS KEMAMPUAN PENALARAN MATEMATIS DALAM PEMECAHAN MASALAH MATEMATIKA SISWA SMP - Maryam, Isnaeni; Lutfiyah, Diyana; Purwaningsih, Wharyanti Ika; Priyadi, Hermawan Gatot (JURNAL MathEdu (Mathematic Education Journal), 2025)
The aim of this research is to analyze mathematical reasoning abilities in solving mathematics problems of junior high school students. This research uses a qualitative description method. The technique for taking subjects is purposive sampling which takes subjects based on certain conditions. The research subjects were 6 students in class VIII of MIBS Middle School in Kebumen. The data collection techniques used were tests, interviews and documentation. The instruments used were mathematical reasoning ability test questions and interviews. The results of this research show that: (1) The mathematical reasoning abilities of students with high mathematical abilities meet the indicators of presenting mathematical statements orally, in writing, in pictures, diagrams and tables, estimating answers and solution processes, calculating rules using certain formulas, and drawing conclusions or generalize; (2) The mathematical reasoning abilities of students with moderate mathematical abilities meet the indicators of presenting mathematical statements orally, in writing, in pictures, diagrams and tables, estimating answers and solution processes, and drawing conclusions or making generalizations; (3) The mathematical reasoning abilities of students with low mathematical abilities do not meet the indicators of mathematical reasoning abilities.